Square Wave Modulation in a Closed-Loop Semiconductor Laser with Optical Feedback (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
We achieve chaotic behavior in the dynamics of a semiconductor laser with ac-coupled optical feedback by experimentally applying a new modulating waveform to the bias current other than a pure sine wave. The embedding technic of the attracter and the quantitative bifurcation diagram analyze the duty cycle and phase effect. The dynamics become chaotic with the increasing values of the duty cycle, and it is chaotic in all values of phase change. Furthermore, the applied square wave modulation gives additional parameters to be tuned, which enhances the security level provided by a closed-loop semiconductor laser with optical feedback.